(untitled) - Pace, Joe (Boston, 2006)
Professional success in the 21st century demands that people work together to achieve their goals. Book Two: Interpersonal Strengths and Leadership, explores and develops the skills that make a person a good teammate and a good leader. This book helps students develop a standard of excellence and pride in work and addresses ethics, trust, respect, strategic thinking, and modeling leadership techniques
Keywords: Teams in the workplace,Work environment,Môi trường làm việc,Quản trị nhân sự